The Educational Failure of Pupils and Students as a Social Phenomenon: A Research Methodology - G. E. Zborovsky; P. A. Ambarova (Высшее образование в России)
The article sets and characterizes the social diagnosis of a significant part of pupils and students, which is defined by the authors as educational failure. It manifests itself in a low level of educational motivation, blurred professional orientations and self-determination, and a weak desire to accumulate human capital and social achievement. This diagnosis can be traced all the way through the transfer of human capital of the unsuccessful educational communities – from school to college and university, and then to the labor market. The article identifies the main lacunae and consequent methodological problems in the study of educational failure. The phenomenon of educational failure is considered in terms of four stages of emergence and development. The features of an interdisciplinary methodology of its research are shown. The authors reveal the potential of the interdisciplinary use of sociological, economic, psychological, socio-psychological, and pedagogical approaches in the study of educational failure and ways to overcome it.